Young people’s health and well-being during the school-to-work transition: a prospective cohort study comparing post-secondary pathways - Reuter, Marvin Alexander; Herke, Max; Richter, Matthias; Diehl, Katharina; Hoffmann, Stephanie; Pischke, Claudia R.; Dragano, Nico (BMC public health, 2022)
At the end of secondary education, young people can either start vocational training, enter university, directly transition to employment or become unemployed. Research assumes that post-secondary pathways have immediate and/or long-term impacts on health and well-being, but empirical investigations on this are scarce and restricted to few countries. Therefore, this study traced the development of health and well-being throughout the highly institutionalised school-to-work transition (STWT) in Germany. We used longitudinal data of the National Educational Panel Study (NEPS), a representative sample of 11,098 school-leavers (50.5% girls) repeatedly interviewed between 2011 and 2020. We estimated the effect of post-secondary transitions on self-rated health and subjective well-being by applying fixed-effects (FE) regression, eliminating bias resulting from time-constant confounding and self-selection into different pathways. A multiple-sample strategy was used to account for the increasing diversity of STWTs patterns. Models were controlled for age, as well as household and residential changes to minimise temporal heterogeneity. Findings indicate that leaving school was good for health and well-being. Compared with participants who did not find a training position after school, direct transitions to vocational training or university were linked to higher absolute levels of health and well-being, but also to a lower relative decline over time. Furthermore, upward transitions (e.g. to programs leading to better education or from unemployment to employment) were associated with improvements in health and well-being, while downward transitions were followed by deteriorations. Findings suggest that school-leave is a sensitive period and that post-secondary pathways provide young people with different abilities to maintain health and well-being. Youth health interventions might benefit when setting a stronger focus on unsuccessful school-leavers.